The one-stage balloon dilatation with stone extraction for a combination of short urethral stricture and urethral stone in men - M. M. Alibekov; M. I. Katibov; A. S. Skorovarov; G. A. Gazimagomedov; K. M. Arbuliev; R. T. Savzikhanov; K. G. Kamalov (Вестник урологии)
Introduction. The literature highlights isolated studies examining approaches to the treatment of patients with a combination of stones and urethral stricture. In this regard, the problem of creating optimal tactics for managing such patients remains relevant.Purpose of the study. To analyze of own experience in treating patients with a combination of stricture and urethral stone using balloon dilation with urethral stone extraction.Materials and methods. The study included 7 men with short urethral stricture and stone, who underwent balloon dilation with urethral stone extraction. The age of patients ranged from 47 to 65 years (median - 52 years). The length of the urethral stricture ranged from 3 to 10 mm (median - 7 mm). The stricture in 2 (28.6%) cases was localized in the penile part of the urethra and 5 (71.4%) in the bulbous part. An etiology of urethral strictures: traumatic - in 2 (42.9%) patients, inflammatory - in 1 (14.3%) of cases, idiopathic - in 4 (57.1%) of cases. All patients had 1 urethral stone. The sizes of the stone ranged from 4 to 9 mm (median - 6 mm).Results. The operation time ranged from 11 to 19 min (median - 13 min). No patient had any intraoperative complications. UTIs was observed in the early postoperative period in 1 patient. The duration of postoperative hospital stay ranged from 1 to 5 days (median - 3 days). Postoperative follow-up ranged from 3 to 24 months (median - 14 months). Only 1 (14.3%) patient had a recurrence of urethral stricture 18 months after treatment. Thus, the overall treatment success in this group of patients was 85.7% (6/7).Conclusion. We used this conjunction approach when combined stricture and urethral stone in men for the first time in the world. It seems quite promising given the results.